A fala e o falo: as mulheres de Fernanda Young e Ivana Arruda Leite - Bastos, Emerson (2021)
The starting of this research is the proposition of speech as a phallic power in female literature. It speaks present in the elaboration of a literature that can provide the opportunity for expression to certain social groups, representativeness and claiming opportunities taken away by privileged groups. The objective of this research is to investigate in the literature how the female characters in the books O pau (2009), by Fernanda Young, and Falo de Mulher (2002), by Ivana Arruda Leite, question and criticize phallocentrism, through their speeches. Speech comes into direct comparison with the psychoanalytic phallus to claim its castrated power. The woman, for decades, was a symbol of psychoanalytic castration when referring to the anatomical perception of the sexes and the silencing of their bodies to stifle their hysterical crises. The speech of these castrated women in the eyes of culture calls to be heard, considered, and, with that, can rebuild other horizons and perspectives on the feminine, because, speech is related to the act of existing and not merely making sounds. When considering the concept of phallus as a neutral signifier and not related only to the penis, would this phallus be the speech used as a literary outlet by these women and the means by which they claim the power of the phallus in their books? What did Freudian women want until the 1930s and what do the women of Fernanda and Ivana want in the 21st century? What social, cultural and political marks can be found in the literature referring to the unfolding of Freudian concepts about femininity? It is through the speak of speech that his characters are used to be read and heard. To compare and analyze the relationship between the literary discourse of female authorship and the Freudian psychoanalytic discourse with its implications for female sexuality, the theoretical framework necessary for the approach will transit between the studies of literary theory with Gonçalves (2005), Bellodi (2005) and Azevedo (2008); the notions of speech and discourse Saussure (2006), Foucault (2012) and Ribeiro (2019); in the field of psychoanalysis Freud (2019), Brennan (1997) and Kehl (2016) on eroticism and femininity, Beauvoir (1980), Branco (1983), Borges (2013) and Preciado (2019), among other writings that will support the understanding of the relations of speech and femininity in literature.